The effects of rear-wheel camber on maximal effort mobility performance in wheelchair athletes - Mason, B.; van der Woude, L.; Tolfrey, K.; Goosey-Tolfrey, V. L. (International Journal of Sports Medicine, 2012)
This study examined the effect of rear-wheel camber on maximal effort wheelchair mobility performance. 14 highly trained wheelchair court sport athletes performed a battery of field tests in 4 standardised camber settings (15°, 18°, 20°, 24°) with performance analysed using a velocometer. 20 m sprint times reduced in 18° (5.89±0.47 s, P=0.011) and 20° camber (5.93±0.47 s, P=0.030) compared with 24° (6.05±0.45 s). Large effect sizes revealed that 18° camber enabled greater acceleration over the first 2 (r=0.53, 95% CI=0.004 to 0.239) and 3 (r=0.59, 95% CI=0.017 to 0.170) pushes compared with 24°. Linear mobility times significantly improved (P=0.05) in 15° (16.08±0.84 s), 18° (16.06±0.97 s) and 20° (16.22±0.84 s) camber compared with 24° (16.62±1.10 s). Although no statistically significant main effect of camber was revealed, large effect sizes (r=0.72, 95% CI=0.066 to 0.250) demonstrated that 18° camber reduced times taken to perform the manoeuvrability drill compared with 15°. It was concluded that 18° camber was the best performing setting investigated given its superior performance for both linear and non-linear aspects of mobility, whereas 24° camber impaired linear performance. This was likely to be due to the greater drag forces experienced. Subsequently, athletes would be recommended to avoid 24° camber and young or inexperienced athletes in particular may benefit from selecting 18° as a starting point due to its favourable performance for all aspects of mobility performance in the current study.